1972
DOI: 10.1037/h0033427
|View full text |Cite
|
Sign up to set email alerts
|

Therapist attitudes as influenced by A-B therapist type, patient diagnosis, and social class.

Abstract: Attempted to clarify a number of inconsistent and contradictory findings regarding interactions between patient diagnosis (schizophrenic vs. neurotic) and the A-B therapist variable. 37 psychiatric residents completed Kemp's version of the A-B scale. The 10 highest and 10 lowest scorers then rated 4 patient vignettes on likability, discomfort, interest in treating, and prognosis. Patient social class as well as diagnosis were systematically controlled. Results support some of the previous research on likabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…These findings suggested that an association may exist between socioeconomic status and therapeutic perceptions of mental illness. Lee and Temerlin (1970) found that when hypothetical clients were described as having lower socioeconomic statuses, they were more likely to be diagnosed as mentally ill by psychiatric residents, results that were affirmed in similar studies by Stein, Green, and Stone (1972) and DiNardo (1975) and in contemporaneous reviews of the literature (Jones, 1974;Lorion, 1974). Nevertheless, by the turn of the millennium, issues of social class, and the potential for associated therapeutic bias had receded from view to the extent that authors in the present decade have commented on the ''near invisibility of the poor in psychology'' (Lott, 2002, paragraph 6), and the neglect of issues of social class even in the context of multicultural competence (Sue & Lam, 2002).…”
Section: Poverty and Mental Health Practicementioning
confidence: 63%
“…These findings suggested that an association may exist between socioeconomic status and therapeutic perceptions of mental illness. Lee and Temerlin (1970) found that when hypothetical clients were described as having lower socioeconomic statuses, they were more likely to be diagnosed as mentally ill by psychiatric residents, results that were affirmed in similar studies by Stein, Green, and Stone (1972) and DiNardo (1975) and in contemporaneous reviews of the literature (Jones, 1974;Lorion, 1974). Nevertheless, by the turn of the millennium, issues of social class, and the potential for associated therapeutic bias had receded from view to the extent that authors in the present decade have commented on the ''near invisibility of the poor in psychology'' (Lott, 2002, paragraph 6), and the neglect of issues of social class even in the context of multicultural competence (Sue & Lam, 2002).…”
Section: Poverty and Mental Health Practicementioning
confidence: 63%
“…Scholars and practitioners (e.g., Bullock, 2004; Goodman, Pugach, Skolnik, & Smith, 2012; Lott, 2002) have argued that mental health practitioners are not immune to making attributions and inferences based on social class. Empirical support for variations in therapist perceptions of clients based upon social class characteristics has also been demonstrated (e.g., Hillerbrand, 1988; Rowden, Michel, Dillehay, & Martin, 1970; Smith, Mao, & Perkins, 2011; Stein, Green, & Stone, 1972). Similar to findings with samples from the general population (e.g., Bullock et al, 2003; Cozzarelli et al, 2001), mental health practitioners were more likely to attribute problems of clients from lower income backgrounds to internal or dispositional factors rather than to external factors (Batson, 1975; Gambrill, 1990; Wills, 1978).…”
Section: Psychotherapist Perceptions and Attributionsmentioning
confidence: 97%
“…Eight hundred clinical psychologists selected from the 1978 American Psychological Association national membership roster, Clinical Psychology Division, served as participants. The case history was a composite of those used in previous research on clinical judgment (Stein et al, 1972) presenting a stimulus client with a general clinical picture of reactive depression. Participants were randomly assigned by replicating sampling to one of the following conditions: (1) 72year-old, working class, male; (2) 72-yearold, working class, female; (3) 72-year-old, middle class, male; (4) 72-year-old, middle class, female; (5) 46-year-old, working class, male; (6) 46-year-old, working class, female; (7) 46-year-old, middle class, male; and (8) 46-year-old, middle class, female.…”
Section: Methodsmentioning
confidence: 99%